Bladder perforations in children - Bakal, U.; Sarac, M.; Tartar, T.; Ersoz, F.; Kazez, A. (Medknow Publications & Media Pvt Ltd, 2015)
Context: Bladder perforations in children occur due to several different reasons. Aim: In this clinical series study, we focused on bladder perforations due to the pelvic injury, and our aim also was to create awareness for a rare type of bladder injuries. Setting and Design: This was a retrospective study of the patients who were treated in our clinic for bladder perforation between 2006 and 2011. Subjects and Methods: We reviewed the documents of childhood bladder perforations, and demographic and clinical characteristics of the patients were obtained. No statistical analyses were used because of the limited number of cases. Results: There were ten patients who suffered from bladder perforation in 5-year period; 5 were male, and 5 were female. The mean age of the patients was 4.35 years. Four patients (40%) experienced iatrogenic perforation and six patients (60%) experienced perforation due to the accident. Common symptoms were hematuria, abdominal tenderness, and inability to urinate. Three patients were diagnosed via emergency laparotomy, without any radiological examinations performed before surgery. Four patients suffered from the intraperitoneal perforation, three patients suffered from extraperitoneal injury and three of them both of intraperitoneal and extraperitoneal injuries. Mean recovery time for patients was 15 days. One patient developed a urinary tract infection and one newborn died due to accompanying morbidities. Nine patients were discharged from the hospital. Conclusion: If the patients had a pelvic injury, surgeons must pay attention for the bladder perforation. Isolated bladder perforations are rare, and they are generally associated with iatrogenic injuries. Clinicians should pay attention to findings such as anuria, inability to insert a urinary catheter, and free fluid in the abdomen in order to diagnose the bladder perforation in newborns. Novice surgeons should pay more attention to avoid causing iatrogenic bladder perforation during inguinal hernia repair.
Keywords: Bladder; child; iatrogenic; perforation; trauma